2011
DOI: 10.3171/2011.9.peds1167
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among magnetic resonance imaging findings, prognostic factors for survival, and histological diagnosis of intrinsic brainstem lesions in children

Abstract: Object The aim of this study was to compare MR imaging characteristics with histopathological findings of intrinsic brainstem lesions and also to show the prognostic factors in patients with diffuse brainstem glioma. Methods Between February 1988 and August 2007, 44 brainstem biopsies were performed at the Roger Salengro Hospital in Lille, France, in children with intrinsic brainstem lesions not amenable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…High-grade pathology (WHO Grade III/IV) has been consistently found to be a predictor of disease progression and death, whereas patients with pilocytic astrocytomas have the most favorable prognosis. 6,12,16,18,20,27 Fisher et al 12 found that pontine location, engulfment of the basilar artery, symptom duration less than 6 months, fibrillary pathology, and abducens nerve palsy on presentation were all associated with worse survival. At 5 years, the survival of patients with pilocytic astrocytoma was 95%, compared with a dismal 15% for patients with fibrillary astrocytomas; however, the researchers did not differentiate focal and diffuse tumors within their patient population and also combined WHO Grade II–IV tumors as fibrillary astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-grade pathology (WHO Grade III/IV) has been consistently found to be a predictor of disease progression and death, whereas patients with pilocytic astrocytomas have the most favorable prognosis. 6,12,16,18,20,27 Fisher et al 12 found that pontine location, engulfment of the basilar artery, symptom duration less than 6 months, fibrillary pathology, and abducens nerve palsy on presentation were all associated with worse survival. At 5 years, the survival of patients with pilocytic astrocytoma was 95%, compared with a dismal 15% for patients with fibrillary astrocytomas; however, the researchers did not differentiate focal and diffuse tumors within their patient population and also combined WHO Grade II–IV tumors as fibrillary astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging and other imaging techniques such as spectroscopy, perfusion, and PET are performed in an attempt to predict the histology of focal brainstem lesions, but a stereotactic biopsy is necessary to distinguish a focal low-grade tumor from a focal malignant tumor and can be conducted with low morbidity. 6,14,17,22 Many investigators have advocated resection as the primary treatment for focal brainstem tumors. 3,9,11,15,16,18,20,21,23,24,27 Some researchers have found that the extent of resection is an important prognostic factor for survival, contrary to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of brainstem lesions in children includes neoplastic, vascular, infectious and postinfectious causes1 2 This case highlights that it is important to include high-grade glioma in the differential of acute brainstem haemorrhage and the essential role of biopsy in establishing the diagnosis.…”
Section: Descriptionmentioning
confidence: 99%
“…[1112131415] Interestingly, our case is unique as he survived for 21 years after histopathological confirmation after diagnosed as brainstem glioma. Prognostic factors affecting survival in the brainstem glioma include age at diagnosis, histopathological type and WHO grade, extent of surgical resection, adjuvant therapy, focal or diffuse lesion, requirement for VP shunt, and associated comorbid illness.…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic factors affecting survival in the brainstem glioma include age at diagnosis, histopathological type and WHO grade, extent of surgical resection, adjuvant therapy, focal or diffuse lesion, requirement for VP shunt, and associated comorbid illness. [1415] Umehara et al . reported a case of pilocytic astrocytoma who received gamma knife therapy 17-years back developed rapid tumor growth during pregnancy necessitating emergency surgery and histopathological diagnosis was pilocytic astrocytoma.…”
Section: Introductionmentioning
confidence: 99%